2021
DOI: 10.7759/cureus.13844
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Diabetes Mellitus and Carpal Tunnel Syndrome: Results From the United States National Ambulatory Medical Care Survey

Abstract: BackgroundCarpal tunnel syndrome (CTS) is the most common compression neuropathy in the upper limb. While various risk factors have been linked to CTS, the role of diabetes mellitus (DM) in the development of CTS remains unclear. Previous studies have failed to consistently demonstrate a clear association between DM and CTS due to variations based on the geographic setting and differences in the study design. The objective of this study was to assess if there is an association between DM and CTS using populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In pervious large cohort studies, the prevalence of DM in patients with CTS ranged from 3 to 5% 18 20 . In one retrospective cohort study in USA, among 1,795 patients with CTS, 254 patients (15%) were diagnosed with DM 21 . The CTS patients combined with DM have been reported as up be to 21% of all CTS patients in a prospective ultrasonographic and electrophysiologic study 2 , which is consistent with our finding.…”
Section: Discussionmentioning
confidence: 99%
“…In pervious large cohort studies, the prevalence of DM in patients with CTS ranged from 3 to 5% 18 20 . In one retrospective cohort study in USA, among 1,795 patients with CTS, 254 patients (15%) were diagnosed with DM 21 . The CTS patients combined with DM have been reported as up be to 21% of all CTS patients in a prospective ultrasonographic and electrophysiologic study 2 , which is consistent with our finding.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 22 reports were excluded with reasons ( Figure 1 ). Finally, 31 studies, consisting of 13 cross-sectional studies [ 10 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], 10 case-control studies [ 11 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], and 8 cohort studies [ 22 , 24 , 25 , 26 , 27 , 55 , 56 , 57 ], were included in the meta-analysis. The characteristics and quality of the included studies are reported in Appendix A Table A2 , Table A3 and Table A4 .…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus (DM) was not found to be associated with bilateral CTS. Interestingly, recent epidemiological studies also found no significant association between DM and CTS [ 27 ].…”
Section: Discussionmentioning
confidence: 99%